PENGEMBANGAN SISTEM INFORMASI UNTUK ADMINISTRASI LAYANAN SURAT DI KELURAHAN BUMIAJI - Suci Cahya Amalia; Yusuf Sulistyo Nugroho (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2023)
One of the various types of written communication tools is a letter, which is divided into official letters and non-official letters. Official letters are used for formal purposes. However, the process of letter administration in Kelurahan Bumiaji, Kabupaten Sragen is still done conventionally, where people who need a letter have to come to the Kelurahan office and queue, which makes the process ineffective. The letter archiving process carried out by the Kelurahan office is also poorly organized. To overcome this problem, in this study, an information system for letter service administration based on a website was created for the Kelurahan Bumiaji office. The method used to develop the system is the software development life cycle (SDLC), with a waterfall process model. The result of this research is the creation of an information system that can assist the community in obtaining the letters needed and assisting in mail services by the Kelurahan Bumiaji. In addition, this information system also displays information such as announcements from Kelurahan and assets owned by the Kelurahan to the public. Black box testing shows that the system can function as it should, and SUS testing obtained an average score of 77.4 and a grade scale B+.